WEFE Leadership Course nurtures transformational female leadership in Nepal - Buchy, Marlene; Koirala, Sanju; Pokharel, Bharat; Pradhan, Meeta S.; Khadka, Manohara (CGIAR, 2024)
NEXUS Gains’ Water–Energy–Food–Ecosystems (WEFE) Leadership Course launched in Nepal in June 2023, with the aim of creating WEFE nexus champions that can advance the uptake of people-centric WEFE approaches, while contributing to greater equality and social inclusion among professionals. In this webinar, facilitators and participants reflect on their experiences of the course.